Fluid-particle interaction in geophysical flows: debris flow - Paleo Cageao, Paloma (2014)
Small scale laboratory experiments were conducted to study the dynamic mor- phology and rheological behaviour of fluid-particle mixtures, such as snout-body architecture, levee formation, deposition and particle segregation effects. Debris flows consist of an agitated mixture of rock and sediment saturated with water. They are mobilized under the influence of gravity from hill slopes and channels and can reach long run-out distance and have extremely destructive power. Better understanding of the mechanisms that govern these flows is required to assess and mitigate the hazard of debris flows and similar geophysical flows. Debris flow models are required to accurately deal with evolving behaviours in space and time, to be able to predict flow height, velocity profiles and run-out distances and shapes. The evolution of laboratory debris flows, both dry glass beads and mixtures with water or glycerol, released from behind a lock gate to flow down an inclined flume, was observed through the channel side wall and captured with high speed video and PIV analysis to provide velocity profiles through out the flow depth. Pore pressure and the normal and shear stress at the base of the flow were also measured.